Can minority shareholders’ “hand-voting” promote green innovation of Enterprises—Empirical evidence from Chinese listed companies - Shi, Xiaofei; Xu, Wenxin; Cao, Xuefen; Hou, Yangshi (Frontiers in Environmental Science, 2023)
China's listed companies have serious Principal-agent problem of the second kind. Large shareholders have violated the rights and interests of minority shareholders in an endless stream of cases. However, the voice of encouraging minority shareholders to actively participate in enterprise decision-making is growing day-by-day. However, there is no consensus on whether the enthusiasm of minority shareholders in decision-making can have a positive impact on enterprises. Therefore, this article takes China' s A-share listed companies from 2016 to 2020 as the research sample, and from the perspective of green innovation, discusses whether the minority shareholders' active participation in enterprise decision-making can improve the level of green innovation of enterprises.The study found that the minority shareholders' active participation in enterprise decision-making can improve the level of green innovation. Moreover, the minority shareholders' "hand voting" improves the green innovation level of enterprises by influencing the media attention; A higher level of legal environment is conducive to strengthening the role of minority shareholders' participation in the shareholders' meeting in green innovation. Based on the property right nature, regional and industrial level, further research found that the minority share-holders' role in improving green innovation capacity is more significant in non-state-owned enterprises, eastern regions and heavy pollution industries. The research results show that minority shareholders, as an important force to monitor the senior executives' behavior and enhance corporate value, actively participate in corporate decisionmaking, can not only improve corporate governance, but also benefit the sustainable development of enterprises.